Intestinal DMT1 Is Essential for Optimal Assimilation of Dietary Copper in Male and Female Mice with Iron-Deficiency Anemia. Issue 8 (3rd August 2018) - Wang, Xiaoyu; Flores, Shireen RL; Ha, Jung-Heun; Doguer, Caglar; Woloshun, Regina R; Xiang, Ping; Grosche, Astrid; Vidyasagar, Sadasivan; Collins, James F
Abstract: Background: Divalent metal-ion transporter 1 (DMT1) may transport copper, but studies to date on this topic have been equivocal. Previously, an ex vivo experiment showed that intestinal copper transport was impaired in Dmt1-mutant Belgrade rats. Objective: In this study, we tested the hypothesis that intestinal DMT1 transports copper in vivo. Methods: Intestine-specific Dmt1 knockout (Dmt1 int/int ) mice and normal (control) littermates (Dmt1 fl/fl ) were used. In study 1, intestinal copper absorption was assessed in 7-wk-old mice of both sexes and genotypes by oral-intragastric gavage of 64 Cu under normal and iron-deficiency anemia (IDA) conditions. In study 2, both sexes and genotypes of 8-wk-old mice were fed diets with adequate iron concentrations [72 parts per million (ppm)] plus adequate (9 ppm) or excessive (183 ppm) copper concentrations for 4 wk. Iron- and copper-related physiologic variables were subsequently assessed. Results: Study 1 showed that intestinal copper transport was enhanced in normal (∼11% increase in males, 35% in females) and anemic (∼42% increase in males, 35% in females) Dmt1 int/int mice. Study 2 showed that, with adequate copper intakes, serum ceruloplasmin (Cp) activity was decreased (by ∼29% in males and 20% in females) and spleens were enlarged (by 3-fold in both sexes) in Dmt1 int/int mice. Higher dietary copper increased hepatic copper concentrations (by ∼3.3-fold in males and 1.5-fold in females), restored serum Cp activity, and mitigated the noted splenomegaly in Dmt1 int/int mice. Conclusions: Copper homeostasis was disrupted in Dmt1 int/int mice, particularly during IDA, despite the noted increases in intestinal copper transport. This was exemplified by the fact that extra dietary copper was required to restore serum Cp activity (a biomarker of copper status) and reduce the severity of the noted splenomegaly (which could reflect changes in erythropoietic demand) in Dmt1 int/int mice. Collectively, these observations show that intestinal DMT1 is essential for the assimilation of sufficient quantities of dietary copper to maintain systemic copper homeostasis during IDA.